Penerapan Digital Iproline: Tinjauan UU ITE dan Perspektif Kekayaan Intelektual - Berliana Tamara Putri; Tasya Safiranita Ramli; Ranti Fauza Mayana (Publikasi Indonesia, 2023)
The growing development of technology has made many changes to human activities, the emergence of products such as artificial intelligence and the internet has a good impact on human life because it can help to streamline the time used. The existence of digital applications used today is not only for entertainment but also for work and official license registration. Like the Iproline application which can be useful for registering Intellectual Property of a creation so that it can be protected. This study aims to determine how the enforcement of digital applications in accordance with the ITE Law and the application of the Copyright Law to digital applications. This research was conducted using a normative juridical approach method which conducts research using literature as research material. Based on the research conducted, the results show that the development of technology that makes digital applications more massively used by the public must be protected based on applicable laws.